The Professionalism of Islamic Education Teachers in Enhancing the Character of High School Students - Dias Edmiliza; Risnita Risnita; Madyan Madyan (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Professionalism of Islamic Education Teachers in Improving the Character of Senior High School StudentsObjective: This study aims to analyse the professionalism of Islamic education teachers in improving student character at SMA Negeri 1 Kota Jambi. Method: This study used a qualitative descriptive method. Data were collected through observation, interviews, and documentation. The research subjects included the school principal, Islamic education teachers, and students. Data analysis was conducted using the interactive analysis model by Miles and Huberman. Results: The social competence of Islamic education teachers significantly influences the formation of students' character. Islamic education teachers possess practical teaching skills, good communication abilities, and the capacity to guide students spiritually, morally, and socially. Conclusion: The professionalism of Islamic education teachers plays an important role in shaping students' character, which requires consistent efforts from teachers, not only in classroom learning but also in the development of moral and spiritual values. Contribution: This study identifies the challenges faced by Islamic education teachers, which can be used as a basis for the development of character education policies in schools, as well as providing practical recommendations for improving the quality of character education at the secondary school level.INDONESIAN: Profesionalisme Guru Pendidikan Agama Islam Dalam Meningkatkan Karakter Siswa Sekolah Menengah AtasTujuan: Penelitian ini bertujuan untuk menganalisis profesionalisme guru Pendidikan Agama Islam (PAI) dalam meningkatkan karakter siswa di SMA Negeri 1 Kota Jambi. Metode: Penelitian ini menggunakan metode deskriptif kualitatif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Subjek penelitian terdiri dari kepala sekolah, guru PAI, dan siswa. Analisis data dilakukan dengan model analisis interaktif dari Miles dan Huberman. Hasil: Kompetensi sosial guru PAI sangat berpengaruh dalam membentuk karakter siswa. Guru PAI memiliki kemampuan mengajar yang efektif, komunikasi yang baik, serta kemampuan dalam membimbing siswa dalam aspek spiritual, moral, dan sosial. Kesimpulan: Profesionalisme guru PAI berperan penting dalam membentuk karakter siswa, yang memerlukan upaya konsisten dari guru, tidak hanya dalam pembelajaran di kelas, tetapi juga dalam pengembangan nilai moral dan spiritual. Kontribusi: Penelitian mengidentifikasi tantangan yang dihadapi oleh guru PAI, yang dapat dijadikan dasar dalam pengembangan kebijakan pendidikan karakter di sekolah-sekolah, serta memberikan rekomendasi yang bermanfaat bagi peningkatan kualitas pendidikan karakter di tingkat sekolah menengah.